Tindak Pidana Pembunuhan Dengan Motif Kehormatan Honor Killing Dalam Perspektif Hukum Pidana Indonesia - Muhtadi, Fachry Saad; Dwi Jayani, Ni Made Ita; Andi Saputra, I Nyoman Octaria; Rahmat Akbar, Muhammad Ardan Aldika; Sulaiman, M Zulfan (Universitas Sang Bumi Ruwa Jurai, 2025)
Honor killing is a complex criminal phenomenon occurring across various cultures, including Indonesia, where values of honor often clash with national criminal law. This study aims to analyze the fulfillment of the elements of murder under the Indonesian Criminal Code (KUHP) in the context of honor killings, examine its legal qualification and sentencing implications, and analyze the dynamics of judicial sanctioning. The research employs a normative legal method with statutory, conceptual, and case law approaches. The results indicate that honor killings fully meet both the objective and subjective elements of murder (Articles 338, 339, 340 of the KUHP), are not recognized as an excuse or justification, and receive no special legal qualification or sentence reduction. Judges consistently reject honor as a juridical mitigating factor and impose penalties proportionate to the crime, affirming the supremacy of law and the protection of the right to life above cultural claims.